High-performance cotton hydrogel-based flexible supercapacitors consisting of graphene / Badawi Nujud Mohammed M - Badawi Nujud , Mohammed M (2023)
The effectiveness of the electrochemical process for supercapacitors has been enhanced by conductive cotton hydrogel with the incorporation of graphene and other ionic contents. The inherently soft nature of cotton mixed with hydrogel provides superior flexibility of the electrolyte, which benefits the devices in gaining high flexibility. Herein, it is reported the current research progress in the field of solid-state hydrogel electrolytes based on 3D pure cotton/graphene and present an overview of the future direction of the research. The ionic conductivity of CGH2 complex hydrogel significantly increased up to 13.9 x 10-3 S/cm at 25 °C due to the presence of graphene which provides a smooth path for the transport of charge carriers and polymer. Furthermore, electrochemical studies were performed by sandwiching the composite hydrogel electrolytes between symmetric cotton-coated graphene electrodes. The electrical conductivity of cotton with different concentrations of graphene was studied. Four-probe method was employed to examine the electrical characteristics of treated cotton electrodes, the graphene coated cotton samples with 17th layers resulted in a surface resistance of 0.644 Ω/sq and retained their maximum resistance even after two months. Thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC) analysis are crucial tools for examining the samples' thermal stability and material degradation pattern. TGA was used to evaluate the thermal stability of the pure cotton sample and the cotton that had been treated with graphene, and the mechanical properties of the composite cotton sample were evaluated by tensile strength test. The fabricated cotton-graphene electrode/ composite hydrogel electrolyte cotton- graphene electrode based symmetric supercapacitor attained the highest specific capacitance of 327 F/g at 3 mVs-1 which was measured by cyclic voltammetry measurement and from galvanostatic charge-discharge measurement, it is obtained a maximum value of 385.4 F/g at 100 mAg-1 current density. The instruments, namely X-ray diffractometer (XRD), Fourier-transform infrared (FTIR) spectroscopy, Raman spectroscopy, Field emission scanning electron microscope (FESEM) have been employed to study the properties of the electrodes and electrolyte, which showed good dispersion of electrode and hydrogel electrolytes samples obtained by dimethyl sulfoxide (DMSO) doping, which reduced the ripple of the cotton. The effectiveness of symmetric supercapacitors fabricated using composite hydrogel electrolytes has been confirmed by powering up a light- emitting diode (LED). Furthermore, the electrochemical analysis demonstrated that cotton- graphene-based hydrogel electrolyte is electrically stable and could be used for the design of next-generation supercapacitors.